Efficacy of Mrudu Samvahana (Forehead Massage) over Takra Dhara (Buttermilk Dripping Therapy) in Anxiety and Stress Induced Essential Hypertension – A Randomized Clinical Trial.: Life Sciences-Ayurveda - Dr. Ashwini Patil; Dr. Pradeep L Grampurohit; Dr. Skandhan K P; Dr. Vinayak B Angadi (International Journal of Life Science and Pharma Research, 2022)
Blood pressure level measuring above 140/90 mm of Hg is termed as hypertension. Hypertension is associated with various risk factors and also is mainly responsible for mortality in industrialized countries. The treatment for hypertension in modern science is palliative in nature. Many of these, along with its effectiveness in controlling the blood pressure, cause adverse side effects; hence the need for the hour is an alternate therapy with no potential side effects. Ayurveda has potential medicines to alleviate hypertension without causing any side effects. The study was to evaluate clinical efficacy of two Ayurveda procedures Mrudu Samvahana and Takradhaara in essential hypertension. The study included a total of 40 patients, attending the Outpatient department of KLE Ayurveda hospital, randomized into Group A and Group B of 20 each. The patients in group A received Mrudu samvaahana with Murchita tila taila which was performed 20 minutes per day for 7 days. The patients in group B received Takra dhara with Amalaki siddha takra which was performed 40 minutes per day for 7 days. Statistical analysis revealed that both groups Mrudu Samvahana and Takradhara showed significant (P<0.0001) results determined by unpaired T test in objective parameters. Between the group assessment. revealed that Takra dhara has shown better results compared to mrudu samvahana in reduction of systolic and diastolic blood pressure. (P<0.0048).